A Genealogy of the Gift - Scalzo, Germán (My University, 2017)
This chapter takes a look at the gift, in which academic interest has recently grown, especially after the release of Benedict XVI’s social encyclical Caritas in Veritate. It outlines a genealogy of the gift, briefly presenting the three main stages of its evolution: (1) the ceremonial gift, typical of the ancient world and found in the cultural anthropological approach that the French tradition later adopted (Mauss, Caillé, Hénaff, etc.); (2) the moral gift, which Aristotle first outlined to explain the emergence of the city; and (3) the personal gift, developed in the Middle Ages thanks to Christian Revelation and its corresponding idea of the person. © Perspectives on Philosophy of Management and Business Ethics
Keywords: Gift; Economics; Mauss; Aristotle; Caritas in Veritate